PENGEMBANGAN FASILITAS TAMAN LANSIA SEBAGAI SARANA LEISURE KELUARGA DI KOTA BANDUNG - ,Zafrullah PURUHITA, - (2011)
Elderly Park is located in Bandung District Wetan, Cibeunying Development Area, the city of Bandung, West Java Province. This park is generally located at an altitude of 791 m above sea level (Bappeda, 2004) with an average temperature of 22.80 º C (CBS, 2005) and as a whole has an area of 16.620 m2 garden with a circumference of 642.5 m (Office of Gardening, 2010) . The form of this park that is elongated with the right Cilaki River dividing the two parks into the west and east, and is dominated by stands of large trees. Elderly Park is one park that is still very beautiful city of Bandung. This research uses descriptive analytical method, the researchers describe in detail without any addition and reduction of data that has been obtained. This research also used a qualitative approach, insrumennya is the researcher himself. In addition, this study uses analysis questionnaire to find out what kind of society against Park perferensi Elderly and footprint analysis as the arrangement of the recommended facilities. Based on the research suggests that visitors want the improvement and development facilities in accordance with the wishes of visitors. The development facilities in the park is strongly influenced by the Office of Elderly Garden City Bandung . Therefore, the government holds a big hand to make the development of facilities in the Garden of the Elderly.